Half a century later, a new species of Wunderlichia (Wunderlichieae, Asteraceae) from the Atlantic Forest inselbergs of Espírito Santo, Brazil - Teles, Aristônio Magalhães; Manhães, Vitor Da Cunha; Couto, Dayvid Rodrigues (Phytotaxa, 2024)
Wunderlichia capixaba, a new species of the tribe Wunderlichieae, Asteraceae family, is described, discussed, and illustrated. The species is currently only found in Pedra dos Cabritos in the community of Barra Alegre, municipality of Castelo, Espírito Santo state, Brazil. It has been categorized as critically endangered. Morphologically akin to W. insignis, W. capixaba distinguishes itself through its synanthous habit (maintaining leaves throughout the flowering period), green involucral bracts (in vivo), dark brown when dried (in sicco), an erect peduncle, approximately 60 florets per capitulum, a nectary longer than wide, and a 3-seriate pappus.